Factors affecting Rhizobium phaseoli-Phaseolus vulgaris symbiosis - Ruschel, Alaides Puppin; Reuszer, Herbert W. (Pesquisa Agropecuaria Brasileira, 2014)
The objectives of this study were to determine the effect of molybdenum and magnesium removal from nutrient solution and combined nitrogen additions on the Rhizobium phaseoli-Phaseolus vulgaris symbiosis; to study the effect of different Rhisobium strain inoculants; to identify any possible correlation between different variables studied; and to relate the acetylene reduction assay to the common method of evaluating nitrogen fixation by legumes by measuring total nitrogen in plants using the Kjeldahl method, and through dry weight of plants. The study was conducted in a greenhouse (3 experiments) at Purdue University, Indiana, U.S.A. The main treatment consisted of withholding molybdenum, magnesium, or both, from free Crone's solution plus micronutrients, or adding combined nitro gen to culture media. The variety "Rico 23", from Brazil, was used. Plants 40 days old were harvested in all experiments. Combined nitrogen added to nutrient media in the different experiments increased the dry weight of plants, percent and total nitrogen in the plant tops, but decreased the weight of nodules and the amount of acetylene reduced to ethylene by excised nodules. Nodules produced by one strain of Rhizobium demonstrated high nitrogenase activity even in treatments with nitrogen. Removal of molybdenum from nutrient solution did not affect dry weight of plant, or nodule weight, but decreased percent of nitrogen of plant tops. Neither molybdenum nor magnesium removal from nutrient solution influenced nitrogen fixation by different strains of Rhizobium used when measured by the acetylene reduction assay or amount of nitrogen in plant tops. In the absence of combined nitrogen the ethylene produced by nodules was positively correlated with both total and percent nitrogen in plant tops, and with the fresh nodule weight, while negative correlations between dry weight of plant tops and other variables (dry weight of entire plant, fresh nodule weight, and acetylene reduced) were found. There was no correlation between acetylene reduction by nodule tissue and the dry weight of entire plant.